Direct Versus Indirect Measurement of Height of The Interproximal Contact Area in Maxillary Anterior Teeth - Shahbaz, Madiha; Khan, Saad; Abbas, Asifa; Iftikhar, Ayesha; Sherazi, Surriya; Khattak, Seema (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare interproximal contact area (ICA) height measurements obtained intraorally with those recorded on dental casts, in order to assess their accuracy and reliability.Study Design: Cross-sectional comparative study.Place and Duration of the Study: Department of Prosthodontics, Armed Forces Institute of Dentistry Rawalpindi, Pakistan from Dec 2024 to May 2025.Methodology: A total of 90 participants with intact maxillary anterior teeth were included. ICA heights were measured intraorally using a digital caliper and compared with corresponding measurements taken on stone casts derived from alginate impressions. ICA was recorded between central incisors (CI–CI), central and lateral incisors (CI–LI), lateral incisors and canines (LI–C), and canines and first premolars (C–FP). Data was analyzed using paired t-tests, with p